Prototipo de detección de expresiones corporales mediante visión artificial para mejorar la comunicación con niños que tienen parálisis cerebral infantil. - Rosales Romero, Cristhian Eduardo (2017)
Currently, much of the technology and its resources have been immersed in the life of the people for improve it, both in style as is its quality; but, about 15% of the world population has some type of disability, among them, the Cerebral Palsy, which has an incidence of 2 to 3 cases per 1000 live births. This small but important group of individuals, especially children, are not able to communicate with ease, and it is here where we take advantage of technology to improve the lives of the same. Every human being is important, and it's understandable the difficulty to be able to help this group of disabled people, through the use of technology; because there are several types of cerebral palsy, with different ways of acting in every person who possesses it, for this reason it is not considered a disease, but as a set of syndromes. This project focuses on investigating a specific case, that is to say, to obtain the knowledge and the necessary conclusions that allow us to improve the communication with an infant who suffers from cerebral palsy, making use of the technology or scientific discipline called Artificial Vision. With the planned research, it seeks to obtain the bodily expressions of the case study, which express an emotion, need or pain; in order to carry out the construction of classifiers based on the technique of Boosting, called AdaBoost; where a cascade of classifiers, built in stages, constitutes a classifier, which will make detections of higher and better level; In order to achieve to develop a prototype detection, understood between an intelligent agent and a mobile application. The prototype is adapted to the ICONIX methodology for their development, where you will find the Requirements Analysis, Analysis and Preliminary Design, Design and Implementation; both for the intelligent agent, in charge of perceiving the bodily expressions of the case study through an IP camera, as for the Mobile Application, whose function is to inform about the same.